HPLC-DAD stability indicating determination of nizatidine in bulk and capsules dosage form - Tarek S. Belal; Mohamed H. Abdel-Hay; Suzy M. Sabry; Ahmed A. Mahgoub (Faculty of Pharmacy, Cairo University, 2013)
This work describes the stability-indicating determination of the H2-receptor antagonist nizatidine in its bulk and capsules dosage form using high performance liquid chromatography coupled with diode array detector (HPLC-DAD). The developed method involved the use of Thermo Hypersil BDS-C8 (4.6 × 250 mm, 5 μm particle size) column and a mobile phase composed of 0.05 M phosphoric acid and acetonitrile (50:50, v/v). The mobile phase was pumped at a flow rate of 1 mL/min. Quantification of nizatidine was based on measuring its peak area at 320 nm. The retention time for nizatidine was about 3.61 min. The reliability and analytical performance of the proposed HPLC procedure were statistically validated with respect to linearity, range, precision, accuracy, specificity, robustness, detection and quantification limits. Calibration curve of nizatidine was linear in the range of 5-50 μg/mL with correlation coefficient >0.9999. The drug was subjected to forced-degradation conditions of acidic and basic hydrolysis, oxidation, dry heat and UV photolysis where it showed considerable degradation in basic and oxidative conditions. The proposed method proved to be specific and stability-indicating by resolution of the drug from its forced-degradation products. The validated HPLC method was applied to the analysis of nizatidine in capsules dosage form where it was quantified with recoveries not less than 98.2%. Assay results were statistically compared to USP 2011 pharmacopeial method where no significant difference was observed between the proposed and reference methods.